Controlled heterogeneous water distribution and evaporation towards enhanced photothermal water-electricity-hydrogen production. (November 2020) - Zhou, Yi; Ding, Tianpeng; Gao, Minmin; Chan, Kwok Hoe; Cheng, Yin; He, Jiaqing; Ho, Ghim Wei
Abstract: The ability to control heterogeneous water distribution and evaporation could address low vapor generation issues which has great implications for distillation and energy systems efficiency. Herein, we devise an efficient solar-driven water-electricity-hydrogen generation system by spatially controlling water diffusion and evaporation of 3D hydrogel evaporators. Specifically, through template-assisted regulation of the interfacial structures of the hydrogel evaporator, the relationship between the macroscale liquid-vapor area and the water pumping pathway was studied. The hybrid wettability and distinct water distribution strategy achieved via selective hydrophobic-hydrophilic modification enhance the photothermal efficiency by 207% compared with the flat hydrophilic evaporator. Finally, the tailored hydrogels for contrasting evaporative cooling and solar absorption heating are integrated with Bi2 Te3 -based thermoelectric generator (TEG) to efficiently convert waste heat into electricity and drive electrochemical water splitting under outdoor sunny/cloudy conditions. The prototype demonstrates evaporation of 1.42 kg m −2  h −1, power output of 4.8 W/m 2, and hydrogen evolution of 0.3 mmol/h. This work could pave the development of highly integrated hybrid systems to deliver three crucial water, energy and fuel commodities for global sustainability. Graphical abstract: Image 1 Highlights: Developed a solar-driven water-energy harvesting system by controlling heterogeneous water distribution and evaporation. 3D pillar structures and microscale pathways are introduced to balance the interfacial heating and water pumping. Hybrid wettability and enlarged liquid-vapor area are actualized and led to 207% photothermal efficiency enhancement. 1.42 kg m −2  h −1 water evaporation, 4.8 W/m 2 power output and hydrogen evolution of 0.3 mmol/h are achieved for outdoor tests.